Cholesterol in autism spectrum disorders - Rafael Franco; Rafael Rivas-Santisteban; Gemma Navarro; Irene Reyes-Resina (Exploration of Neuroprotective Therapy, 2021)
The autism spectrum disorder (ASD) comprises a series of neurological diseases that share serious alterations of the development of the central nervous system. The degree of disability may vary so that Asperger’s may have a relatively normal life and get positions of responsibility in corporations and even in Governments, whereas other ASD sufferers are fully dependent on caregivers and have serious cognitive deficits. Although the first cases of autism were detected by looking at failures in metabolism, e.g., phenylketonuria, to later identify the faulty gene, today the trend is the opposite, first obtaining the exome and minimizing the look for altered parameters in blood, urine, etc. Cholesterol is key for neural development as it is not able to cross the blood brain barrier. Therefore, any gene or environmental factor that affects cholesterol synthesis will impact early developmental stages eventually leading to a disease within the autism spectrum and/or schizophrenia. This review provides data of the relevance of cholesterol dyshomeostasis in autism spectrum disorders. Determining biochemical parameters in body fluids should help to provide new therapeutic approaches in some cases of autism.